2016
DOI: 10.21577/0103-5053.20160312
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Screening of Endophytic Fungi Isolated from the Aerial Parts of Paepalanthus chiquitensis (Eriocaulaceae) Led to the Isolation of Secondary Metabolites Produced by Fusarium fujikuroi

Abstract: The screening for antimicrobial activity of twenty five endophytic fungi isolated from the aerial parts of Paepalanthus chiquitensis (Eriocaulaceae) was assayed against the bacteria Grampositive Staphylococcus aureus, Gram-negative Escherichia coli and Salmonella setubal, and the yeast fluconazole-resistant Candida albicans. The ethyl acetate extract produced by Fusarium fujikuroi was the most bioactive and this fungus was chosen for the chemical study, affording the isolation of an alkaloid 2-(4-butylpicolina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
(21 reference statements)
0
8
0
1
Order By: Relevance
“…This chemical study yielded an alkaloid 2-(4-butylpicolinamide) acetic acid ( 171 ) and three known compounds: fusaric acid ( 172 ), indole acetic acid ( 173 ), and terpestacin ( 174 ). The minimal inhibitory concentration of the extract, fusaric acid, and indole acetic acid had values from 125 to 1000 μg mL −1 [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…This chemical study yielded an alkaloid 2-(4-butylpicolinamide) acetic acid ( 171 ) and three known compounds: fusaric acid ( 172 ), indole acetic acid ( 173 ), and terpestacin ( 174 ). The minimal inhibitory concentration of the extract, fusaric acid, and indole acetic acid had values from 125 to 1000 μg mL −1 [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, only 2 studies have been reported in the literature involving the evaluation of secondary metabolites from strains of endophytic fungi isolated from Paepalanthus sp. (Eriocaulaceae) and which have exhibited antimicrobial activity potential [5,6].Paraphaeosphaeria sp. (Ascomycota: Montagnulaceae) are ubiquitous fungi that are present in soil as well as in various plants in different habitats [7].…”
mentioning
confidence: 99%
“…To date, only 2 studies have been reported in the literature involving the evaluation of secondary metabolites from strains of endophytic fungi isolated from Paepalanthus sp. (Eriocaulaceae) and which have exhibited antimicrobial activity potential [5,6].…”
mentioning
confidence: 99%
“…In another aspect, F. fujikuroi is an industrial fungi used for the production of gibberellic acids, a group of extensive phytohormones (Cen et al, 2020). Extraction of secondary metabolites of F. fujikuroi led to the identification of alkaloid 2-(4-butylpicolinamide) acetic acid, terpestacin, and fusaric acid, among them only fusaric acid was moderately active against S. aureus, E. coli, and Salmonella setubal (Hilário et al, 2016). Given that 45 putative gene clusters were reported in F. fujikuroi using wholegenome sequencing (Wiemann et al, 2013), the possibility of exploiting new secondary metabolites with antibacterial and anticancer activity is still promising.…”
Section: Identification Of the Bioactive Strain Wqf5mentioning
confidence: 99%